A Nurse’s Role to Develop Health Media for Pre-school Children in Naresuan University Demonstration School (Kindergarten and Primary) During the COVID-19 Pandemic - Yunak, Ratanachadawan; Patamadilok, Sudakarn; Chanbanchong , Chantana; Bunying, Varintorn; Pakdeewong , Panuwat; Udomrat , Thak (Journal of The Royal Thai Army Nurses, 2022)
Pre-school children are higher risk to COVID-19 than toddlers and school-age children because they begin spending much time for social contacts in daily living. However, since their cognitive ability is in concrete level, pre-school children are limited to scientific reasons of COVID-19 pandemic and new normal living. Naresuan University Demonstration School (Kindergarten and Primary) developed health media for the sake of children to be safe from COVID-19 and not to spread out the virus if they were infected. Based on child development concepts, through the process of developing the media, a nurse’s roles were training teachers to perform health communication, determining a scope of contents, making languages concrete, and designing how the media were presented. The process, definitely, illustrated roles of a school nurse to promote a child’s health literacy and skills to protect themselves from infectious diseases by integrating health science as well as play to learn concept in the Early Childhood Curriculum. A nurse should teach a child to understand how the disease transmits through certain body organs. Contact precaution should be transcribed into concrete language, cartoons, or story-telling. Teachers should be promoted to integrate contact precaution skills in classes and routine activities at schools. Families and teachers should be encouraged to be role models for children. New normal living and hygiene skills among children should be used as a part of nursing outcome indexes.